Clinicopathologic significance of the expression of Snail in hepatocellular carcinoma - Woo, Hyun Young (The Korean Association for the Study of the Liver, 2011)
BACKGROUND/AIMS: E-cadherin is involved in intercellular binding and cellular polarity formation. Snail is a key regulator of the epithelial-mesenchymal transition and is closely associated with tumor invasiveness due to its ability to suppress E-cadherin expression. We investigated the expressions of E-cadherin and Snail in hepatocellular carcinoma (HCC) tissue to determine the clinical significance of these proteins in HCC. METHODS: Immunohistochemistry was used to examine the expressions of E-cadherin and Snail in resected tissues from 59 patients diagnosed with HCC. We also evaluated the relationship between the expressions of these two molecules in HCC tissue and clinicopathologic factors in the patients. RESULTS: Immunohistochemistry showed that Snail was stained in 20.3% of the HCC tissues and 3.4% of noncancerous tissues. Snail was not stained in the area of E-cadherin expression. The expression of Snail in the HCC tissue was associated with poorly differentiated HCC (P=0.028). The expression of Snail without E-cadherin staining in HCC tissue was significantly associated with postoperative HCC recurrence (P=0.013). CONCLUSIONS: The expression of Snail in HCC tissue was associated with decreased expression of E-cadherin and poorly differentiated HCC. The expression of Snail without E-cadherin staining in HCC was associated with postoperative recurrence.